COVID-19 AS A SPRINGBOARD TO A JUST AND GREEN FUTURE? THE ROLE OF SOCIAL WORK - Mulvale, James (Canadian Social Work Review / Revue canadienne de service social)

(untitled) (Canadian Association for Social Work Education / Association canadienne pour la formation en travail social (CASWE-ACFTS), 2022)
The devastation of the COVID-19 pandemic taught us vital public policy lessons in Canada about the necessity of public healthcare, the feasibility of universal and unconditional income support, and the urgency of moving towards a new post-growth economy that is in harmony with the environment and allows people to control their time and life choices. Social work has a key role to play in helping us to navigate our way past the pandemic emergency and towards such a radical new vision of an economically just and ecologically sustainable Canadian society.